Studi Kualitatif Tentang Peran Filsafat Ekonomi Islam dalam Pengelolaan Sumber Daya Alam - Ahmad Wahyudi Zein; Elvira Andriyani; Adisty Aulia Zahra; Widya Anggraini (Universitas 45 Surabaya, 2025)
This study aims to analyze the role of Islamic economic philosophy in the management of natural resources using a qualitative approach. Islamic economic philosophy offers a holistic and transcendental perspective that integrates spiritual, moral, and social values into every aspect of the economy, including natural resource management. This research employs a descriptive qualitative method with data collection techniques such as literature reviews, in-depth interviews, and participatory observations. Data were analyzed using thematic analysis to identify key patterns and principles of Islamic economic philosophy relevant to natural resource management. The findings reveal that Islamic economic philosophy emphasizes justice, sustainability, and social responsibility as the primary foundations for managing natural resources. These principles are reflected in the concepts of trust (amanah), benevolence (ihsan), and public benefit (maslahah), which guide the responsible utilization of natural resources for collective welfare without compromising environmental balance. Moreover, spiritual values such as monotheism (tauhid) and awareness of accountability before Allah SWT motivate individuals and institutions to manage natural resources ethically and sustainably. Thus, this study contributes to the development of new insights into how Islamic economic philosophy can serve as an alternative solution to addressing challenges in natural resource management in the increasingly complex modern era.